Synthesis and characterization of forsterites for potential use as cathode materials in magnesium battery / Siti Hafizha Tamin - Siti Hafizha , Tamin (2018)
Following the achievements in the field of lithium battery, there have been more and more attempts over the years to develop magnesium rechargeable batteries. However, the development of magnesium rechargeable batteries was hindered because of the difficulty to realize fast Mg2+ transport in the host cathode material. Recently, orthosilicate cathode materials have gained considerable attention because of their structural stability and high reversible capacity. This type of materials have been widely investigated and successfully applied in lithium rechargeable batteries. Herein, orthosilicate Mg2SiO4 have been proposed as potential cathode material in rechargeable magnesium batteries. Doping approach has been employed in this work to improve the structural and morphological properties of Mg2SiO4 materials hence enhancing the performance of cathode materials. Sol-gel method has been employed to synthesize Mg2SiO4 and Mg2SiO4 doped materials. Mg2SiO4 compound was chosen as the parent compound in this work and was addressed as System I. The X-ray diffraction result shows the formation of pure orthorhombic Mg2SiO4 crystal structure with a = 10.1693 Å, b = 5.9685 Å and c = 4.6886 Å. Sample sintered at 1100 °C has the largest unit cell volume V = 284.5759 Å3 which provide more space for magnesium ion transfer and owned the smallest Rct = 7.01 × 108 Ω. CV results show that the electrochemical process consists of two pairs of redox peaks.. System II has been prepared based on stoichiometric Mg2-xMnxSiO4. Effect of Mn doping on the structural, morphological and electrochemical properties were investigated. X-ray diffraction results show that Mn doping does not destruct the lattice structure of the compound for x ≤ 0.6. The introduction of Mn2+ considerably improves the structural and morphological properties of the parent compound hence enhancing the electrochemical properties of the compound. Sample with x = 0.6 has the largest unit cell volume V = 296.0189 Å3 and smallest Rct = 2.15 × 108 Ω. CV result show that Mg2-xMnxSiO4 could be a good host for Mg2+ intercalation, and a potential cathode material for magnesium batteries. Zr4+ doped Mg1.8Mn0.2SiO4 (Mg1.8Mn0.2Si1yO4Zry, 0.0 ≤ y ≤ 0.4) samples were prepared and assigned as System III. X-ray diffraction patterns of the materials exhibited no extra peak for y ≤ 0.3 indicated that Zr entered the structure rather than forming impurities. Zr doping contributed to the enhancement of the electrochemical performance of Mg1.8Mn0.2SiO4. For this work, Mg1.8Mn0.2Si0.7O4Zr0.3 which possessed the largest unit cell volume, V = 297.5823 Å3 have the smallest Rct, suggesting that the electrode possesses an easier charge transfer process than the other. A pair of anodic and cathodic peak can be distinguished from voltammogram of Mg1.8Mn0.2Si0.7O4Zr0.3 indicates that intercalation and deintercalation process proceed via one stage. Results show that Zr doping improved the electrochemical performance of Mg1.8Mn0.2SiO4 and this material can be used as cathode in magnesium batteries. Results show that Mg2SiO4 and Mg2SiO4 doped materials could be a potential cathode material for magnesium batteries and this works could be extended to obtain promising cathode materials.